Name, Shame and Blame: Criminalising Consensual Sex in Papua New Guinea - Stewart, Christine (ANU Press, 2014)
This book is an exceptional contribution to our knowledge of the nexus between the criminal law and negative attitudes of society, and what effects criminalization has on the social lives of prostitutes and males who have sex with males, and whether these effects might provide evidence to support the argument for law reform.